Vertical transmission of highly similar blaCTX-M-1-harbouring IncI1 plasmids in Escherichia coli with different MLST types in the poultry production pyramid - Zurfluh, Katrin; Wang, Juan; Klumpp, Jochen; Nüesch-Inderbinen, Magdalena; Fanning, Seamus; Stephan, Roger (Frontiers in Microbiology, 2014)
Objectives: The purpose of this study was to characterize sets of ESBL-producing Enterobacteriaceae collected longitudinally from different flocks of broiler breeders, meconium of one-day-old broilers from theses breeder flocks, as well as from these broiler flocks before slaughter. Methods: Five sets of ESBL-producing E. coli were studied by multi-locus sequence typing (MLST), phylogenetic grouping, PCR-based replicon typing (PBRT) and resistance profiling. The blaCTX-M-1-harbouring plasmids of one set (pHV295.1, pHV114.1 and pHV292.1) were fully sequenced and subjected to comparative analysis. Results: Eleven different MLST sequence types (ST) were identified with ST1056 the predominant one, isolated in all five sets either on the broiler breeder or meconium level. Plasmid sequencing revealed that blaCTX-M-1 was carried by highly similar IncI1/ST3 plasmids that were 105 076 bp, 110 997 bp and 117 269 bp in size, respectively. Conclusions: The fact that genetically similar IncI1/ST3 plasmids were found in ESBL-producing E. coli of different MLST types isolated at the different levels in the broiler production pyramid provides strong evidence for a vertical transmission of these plasmids from a common source (nucleus poultry flocks).